What Is an L-Cell and How Do We Study the Secretory Mechanisms of the L-Cell? - Kuhre, Rune E.; Deacon, Carolyn F.; Holst, Jens J.; Petersen, Natalia (Frontiers in Endocrinology, 2021)
Synthetic glucagon-like peptide-1 (GLP-1) analogues are effective anti-obesity and anti-diabetes drugs. The beneficial actions of GLP-1 go far beyond insulin secretion and appetite, and include cardiovascular benefits and possibly also beneficial effects in neurodegenerative diseases. Considerable reserves of GLP-1 are stored in intestinal endocrine cells that potentially might be mobilized by pharmacological means to improve the body’s metabolic state. In recognition of this, the interest in understanding basic L-cell physiology and the mechanisms controlling GLP-1 secretion, has increased considerably. With a view to home in on what an L-cell is, we here present an overview of available data on L-cell development, L-cell peptide expression profiles, peptide production and secretory patterns of L-cells from different parts of the gut. We conclude that L-cells differ markedly depending on their anatomical location, and that the traditional definition of L-cells as a homogenous population of cells that only produce GLP-1, GLP-2, glicentin and oxyntomodulin is no longer tenable. We suggest to sub-classify L-cells based on their differential peptide contents as well as their differential expression of nutrient sensors, which ultimately determine the secretory responses to different stimuli. A second purpose of this review is to describe and discuss the most frequently used experimental models for functional L-cell studies, highlighting their benefits and limitations. We conclude that no experimental model is perfect and that a comprehensive understanding must be built on results from a combination of models.